Superconductivity Volume 1: Conventional and Unconventional Superconductors Volume 2: Novel Superconductors - Bennemann, Karl-Heinz.; Ketterson, John B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Conceived as the definitive reference in a classic and important field of modern physics, this extensive and comprehensive handbook systematically reviews the basic physics, theory and recent advances in the field of superconductivity. Leading researchers, including Nobel laureates, describe the state-of-the-art in conventional and unconventional superconductors at a particularly opportune time, as new experimental techniques and field-theoretical methods have emerged. In addition to full-coverage of novel materials and underlying mechanisms, the handbook reflects continued intense research into electron-phone based superconductivity. Considerable attention is devoted to high-Tc superconductivity, novel superconductivity, including triplet pairing in the ruthenates, novel superconductors, such as heavy-Fermion metals and organic materials, and also granular superconductors. What’s more, several contributions address superconductors with impurities and nanostructured superconductors. Important new results on current problems are presented in a manner designed to stimulate further research. Numerous illustrations, diagrams and tables make this book especially useful as a reference work for researchers, students and teachers. Treating the entire superconductivity field, this unparalleled reference resource carefully blends theoretical studies with experimental results to provide the scientist and engineers an indispensable foundation for further research.
History of Superconductivity: Conventional, High-Transition Temperature and Novel Superconductors -- Phenomenology and Microscopic Theory: Theoretical Foundations -- Electron-Phonon Superconductivity -- Coexistence of Singlet Superconductivity and Magnetic Order in Bulk Magnetic Superconductors and SF Heterostructures -- Theory of Superconducting Alloys -- Impurity Nanostructures and Quantum Interference in Superconductors -- Nanostructured Superconductors -- Proximity-Coupled Systems: Quasiclassical Theory of Superconductivity -- Principles of Josephson-Junction-Based Quantum Computation -- Fluctuation Phenomena in Superconductors -- Universal Properties of Cuprate Superconductors: Evidence and Implications -- Vortex Matter -- Unconventional Superconductivity in Novel Materials -- High-T c Superconductivity -- Tunneling Spectroscopy of Conventional and Unconventional Superconductors -- Phase-Sensitive Tests of Pairing Symmetry in Cuprate Superconductors -- Photoemission in the High-T c Superconductors -- Neutron Scattering and the Magnetic Response of Superconductors and Related Compounds -- Heavy-Fermion Superconductivity -- Organic Superconductors -- Concepts in High Temperature Superconductivity -- A Spin Fluctuation Model for d-Wave Superconductivity -- Electronic Theory for Superconductivity in High-T c Cuprates and Sr2RuO4 -- Superfluid 3He and the Cuprate Superconductors.
Keywords: Superconductivity; Superconductors; Condensed matter; Engineering; Optical materials; Electronic materials; Strongly Correlated Systems, Superconductivity; Condensed Matter Physics; Engineering, general; Optical and Electronic Materials